New Experimental Model of Terminal Aneurysms in Swine: Technical Note - Yatomi, Kenji; Yamamoto, Munetaka; Mitome-Mishima, Yumiko; Nonaka, Sensyu; Yoshida, Kensaku; Oishi, Hidenori; Arai, Hajime (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2012)
Background Animal models of intracranial aneurysms are important for training surgeons and creating innovative endovascular treatment. Swine have physical dimensions close to those of humans and so are widely used in cardiology research. swine used as models for intracranial aneurysms have had difficulty maintaining long-term aneurysm patency. We present a swine model that may allow researchers to follow long-term outcomes after endovascular treatment.Materials and Methods We developed a terminal aneurysm model in swine (n = 3) using a vein pouch of an end-to-side anastomosis of the right carotid artery. We anastomosed the left carotid artery end and the right carotid artery side, designing it so the blood flows into the aneurysmal neck directly from the opposite side. we also anastomosed the ascending cervical artery and the right carotid artery, with flow reversal in the proximal right carotid artery by ligating the more proximal side. At the same time, a side-wall aneurysm was made, and we compared their patency periods.Results The terminal aneurysms remained patent for 3 months, and there were no major changes in their size or shape. In contrast, the side-wall aneurysms had become occluded at the 1-month follow-up.Conclusion Our swine model displayed long-term patency and has the potential to allow long-term evaluation of new techniques and embolic agents.
Keywords: intracranial aneurysm; experimental model; saccular; terminal aneurysm; swine